Introduction to Special Topic Forum: Advancing and Expanding Work-Life Theory from Multiple Perspectives - Powell, Gary N.; Greenhaus, Jeffrey H.; Allen, Tammy D.; Johnson, Russell E. (Academy of Management Review, 2019)
Research on the work-life interface has exploded over the past five decades because of trends in the nature of gender roles, families, work, and careers. However, work-life theory has not kept up with the explosion in research. The purpose of this special topic forum is to offer a corrective by developing new theory to make sense of the research to date and to guide future research. The six articles in this forum make substantial contributions to work-life theory individually and collectively. They provide useful guidance for future work-life theory and research from multiple theoretical perspectives that vary in their level of analysis and in their focus on decision making, diversity, and temporal dynamics. In addition, these six articles offer innovative implications for practice by employees, couples, supervisors, organizations, communities, and societies.